(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
In the article, the authors investigate the effect of the wind load at the frank of the building on the stress-strain state of the roof trusses in the end brace blocks. Traditionally, to perceive the wind pressure to the frank of the building, in the lower zones of the roof trusses, horizontal joint trusses were arranged on the half-timbered columns by means of sheet hinges. The belts of these brace trusses were the lower belts of the roof trusses themselves, and the grid was designed additionally. Further, the support reactions of the horizontal brace trusses from the wind load, through braces in the plane of the columns, were transferred to the foundation. However, the question that the lower belt of the roof truss performs the functions of a belt and a brace truss and that the forces from the vertical load are combined in it, was not considered. Therefore, it is necessary to evaluate the effect of wind pressure at the flank of an industrial building on the stress-strain state of brace trusses in end brace blocks. The authors are developing a method for the quantitative assessment of the effect of wind pressure on the flank of industrial buildings on the stress-strain state of roof trusses in end brace blocks. The efforts in brace trusses are determined in the lower belts of the roof trusses from concentrated single forces of wind pressure to the flake of the industrial building, applied at the nodes of the lower belt of the roof trusses - at the level of the sheet hinges on the half-timbered columns at the ends of the building. The authors consider the geometric patterns of brace trusses along the lower belts of the roof trusses with the efforts in their elements from a unit nodal load of wind pressure to the flake of an industrial building for typical spans of 18, 24, 30, and 36 m. It is easy to evaluate the effect of wind pressure on the stress-strain state of the roof trusses in the coupling end blocks, having obtained unit efforts in the elements of brace trusses for any typical spans. For example, an industrial building with a span of 36 m and a 6 m step of bent located in Kramatorsk is considered. For a brace truss with a span of 36 m, the maximum tensile force in the belt from a single horizontal nodal load and the actual one were found. It should be noted that the function of the belt of the brace truss is performed by the lower belt of the roof truss, the load bearing capacity of which, taking into account the calculated ultimate load, was 3%. But the effort in the lower belt of the roof trusses in the end brace block increases due to wind pressure at the flank of the building. The combination of two functions in the element of the lower belt leads to a change in the stress state - overwork in the lower belt was 27%. To the roof trusses of the industrial buildings in end brace blocks, a special approach is needed in assessing the stress-strain state in them. The proposed methodology makes it possible to assess the stress-strain state of the typical spans roof trusses of industrial buildings in end brace blocks.